Изотопы углерода и кислорода в карбонатах амфиболовых метасоматитов Сергеевского месторождения золота (Украинский щит) - Фомин, Ю.А.; Демихов, Ю.Н. (Видавничий дім "Академперіодика" НАН України, 2007)
The C, O isotope composition of carbonates in the gold-bearing amphibol metasomatites have been investigated: δ13C and δ18O (‰) correspondingly for calcite 0...–1.9 and +12.2...+9.0; for dolomite –0.6...+3.3 and +16.4...+9.1. The trends of these characteristics changing in the different metasomatic zones in the temperature range 240–130 °C and the genetic peculiarities of Ca–Fe–Mg contact-metasomatic system are considered.